Answer:
y=x-5
Step-by-step explanation:
Answer:
4j^3 + 5j^2 + 7j - 1
Step-by-step explanation:
(8j^3 - 3j^2 + 5)-(4j^3+8j^2+7j-6)
Distribute the -1 in front of the (4j^3+8j^2+7j-6)
8j^3 - 3j^2 + 5 - 4j^3 + 8j^2 + 7j - 6
We can combine anything with the same exponent number that "j" is raised to
8j^3 - 4j^3 = 4j^3
-3j^2 + 8j^2 = 5j^2
7j is just 7j since there is nothing else with just j in it
5 - 6 = -1
Add these together
4j^3 + 5j^2 + 7j - 1 is our final answer
idk
Step-by-step explanation:
Answer:
y=mx+c
We have to find the value of m and c.
Let's substitute the value of x and y from the table.
When x=1, y=15,
15= m(1)+c
m +c= 15 ------(1)
Now substitute another set of x and y values.
When x=2, y=24,
24= m(2)+c
2m +c= 24
c= 24 -2m ------(2)
Let me rewrite the two equations so that it is clearer for you to see.
m + c= 15 -----(1)
c = 24 -2m -----(2)
subst. (2) into (1):
m+ 24-2m= 15
-m= 15-24 (bring constants to 1 side, m terms to the other)
-m= -9 (simplify)
m= 9 ( divide by -1 throughout)
subst. m=9 into (2):
c= 24 -2(9)
c= 24-18
c= 6
Thus, the equation is y=9x+6.
When the cat is 3 years old, x=3.
When x=3,
y= 9(3)+6
y= 33.
Hence, the cat is 33 years old in human years.